Physical perfection of students of educational institutions law enforcement by means of outdoor games - N.B. Kutergin; A.I. Tkachenko; A.N. Kulinichev (Physical Education of Students, 2013)
We consider the means and methods of use of outdoor games in physical perfection of students. Highlighted in the direction of professionally-applied physical skills of students. Proposed systematization of outdoor games. The brief content of the big games and the average mobility. Proposed themes and a summary of the single combat with the use of outdoor games. Particular consideration when choosing outdoor games should be given their focus on the development of skills to move freely on the carpet, the tackler and be free of seizures opponent chase the opponent. For strength training are recommended games that require short-term display of speed and power voltages of moderate load. For the development of endurance recommended games with multiple repetition of actions, with continuous motor activity.